2021
DOI: 10.1186/s40168-021-01089-8
|View full text |Cite
|
Sign up to set email alerts
|

Remodeling of the maternal gut microbiome during pregnancy is shaped by parity

Abstract: Background The maternal microbiome has emerged as an important factor in gestational health and outcome and is associated with risk of preterm birth and offspring morbidity. Epidemiological evidence also points to successive pregnancies—referred to as maternal parity—as a risk factor for preterm birth, infant mortality, and impaired neonatal growth. Despite the fact that both the maternal microbiome and parity are linked to maternal-infant health, the impact of parity on the microbiome remains … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
51
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(60 citation statements)
references
References 88 publications
6
51
0
Order By: Relevance
“…Our data indicate that the maternal microbiome was less rich (lower observed ASVs) but more heterogeneous (increased within group dissimilarity, beta diversity) during pregnancy. This increase in beta-diversity with pregnancy is in line with data from multiple human and animal studies, particularly late in pregnancy (18)(19)(20)37). On the other hand, previous clinical studies have reported a drop, an increase, or no change in the alpha diversity of the maternal microbiome (18,19,35) likely due to the high heterogeneity within the healthy human microbiome (36).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our data indicate that the maternal microbiome was less rich (lower observed ASVs) but more heterogeneous (increased within group dissimilarity, beta diversity) during pregnancy. This increase in beta-diversity with pregnancy is in line with data from multiple human and animal studies, particularly late in pregnancy (18)(19)(20)37). On the other hand, previous clinical studies have reported a drop, an increase, or no change in the alpha diversity of the maternal microbiome (18,19,35) likely due to the high heterogeneity within the healthy human microbiome (36).…”
Section: Discussionsupporting
confidence: 87%
“…The gut microbiome plays critical roles in vitamin production (11), immune homeostasis (12), and metabolism of indigestible substrates among others (13). This community stabilizes in adulthood (14), but sensitive to environmental factors such as dietary shifts (15), antibiotic use (16), and other shifts in host physiology such as pregnancy (18). Early studies found that the pregnancy gut microbiome is less diverse, more variable, and harbors an increased abundance of Proteobacteria (19).…”
Section: Introductionmentioning
confidence: 99%
“…Second, the correlation between maternal parity and maternal age raises the question of whether the relationships described here may reflect age, rather than parity, effects. Because our hypotheses were centered on the effects of successive reproductions on maternal communities, and because prior work has shown that parity, not age, shapes the maternal microbiota ( Berry et al., 2021 ), we did not include maternal age in our analyses to avoid issues of multicollinearity. Instead, we focused on parity because successive reproductions (independent of maternal age) shape the morphology of both the mammary gland ( Rovai et al., 1999 ) and variation in milk production across mammalian species (e.g., Lang et al., 2012 ; Sevi et al., 2000 ), suggesting that similar effects may be found in maternal milk and infant gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…More broadly, the maternal environment may program the infant gut microbiota for enhanced milk utilization via vertical microbial transmission. Thus far, parity effects on maternal microbiota have been demonstrated in agricultural species ( Berry et al., 2021 ; Bogado Pascottini et al., 2021 ), and more recently in humans ( Kervinen et al., 2021 ; Lopez Leyva et al., 2021 ). However, in pigs, parity effects extend to the infant gut microbiota, suggesting that such effects may be vertically transmitted from maternal reservoirs ( Berry et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation